Diastereoselective synthesis of functionalized spiroindolines via intramolecular ipso-iodocyclization/nucleophile addition cascade reactions of indole-tethered ynones - Bag, Debojyoti; Sawant, Sanghapal D. (Organic and biomolecular chemistry, 2024)
Herein, we describe a highly diastereoselective approach for synthesizing polyfunctionalized spiroindolines from indolyl-ynones involving an ipso-iodocyclization/nucleophile addition cascade. The developed strategy allows the formation of a spirocyclic core and the installation of two functional groups in a single operation. Also this strategy is accompanied by the generation of two C-C and one C-I bonds and two contiguous stereocenters.